2011
DOI: 10.4103/0971-6866.92104
|View full text |Cite
|
Sign up to set email alerts
|

Risk conferred by FokI polymorphism of vitamin D receptor (VDR) gene for essential hypertension

Abstract: BACKGROUND:The vitamin D receptor (VDR) gene serves as a good candidate gene for susceptibility to several diseases. The gene has a critical role in regulating the renin-angiotensin system (RAS) influencing the regulation of blood pressure. Hence determining the association of VDR polymorphisms with essential hypertension is expected to help in the evaluation of risk for the condition.AIM:The aim of this study was to evaluate association between VDRFok I polymorphism and genetic susceptibility to essential hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…In the present study AA/GA carriers tended to suffer more frequently from osteoporosis, a difference, however, not reaching statistical significance. VDR rs2228570 polymorphisms have further been shown to impact on blood pressure and prevalence of hypertension [26]. Vitamin D deficiency may limit mobility in community dwelling older adults [74], which may impact on instrumental activity of daily life (IADL)-score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study AA/GA carriers tended to suffer more frequently from osteoporosis, a difference, however, not reaching statistical significance. VDR rs2228570 polymorphisms have further been shown to impact on blood pressure and prevalence of hypertension [26]. Vitamin D deficiency may limit mobility in community dwelling older adults [74], which may impact on instrumental activity of daily life (IADL)-score.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of VDR have been reported to be associated with bone mineral density [23] diabetes mellitus [24,25], hypertension [26], asthma [27,28], periodontitis [29,30], risk of multiple sclerosis [31,32] and malignancy [33,34,35,36,37,38]. On the other hand, several studies failed to report an impact of VDR polymorphisms on multiple sclerosis [39], inflammatory bowel disease [40], coronary artery disease [41] or malignancy [42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…BsmI polymorphism of the VDR gene was found to influence blood pressure in healthy men, while a positive relationship was noted between 25(OH)D 3 levels and blood pressure only in men and not women with the BB genotype [125]. A study on an Indian cohort also found important associations between hypertension and Fok I VDR polymorphism [rs2228570], which generates long and short variants of the VDR, independent of sex, family history and smoking [126,127]. However, allelic frequencies and genotype distribution of FokI and BsmI VDR polymorphisms were not found associated with hypertensive status or renin activity in a small study on Italian individuals with essential hypertension [128].…”
Section: Vitamin D and Arterial Hypertensionmentioning
confidence: 99%
“…Полученные нами результаты согласуются с данными литературы, указывающими на ассоци-ацию риска развития ССЗ, а именно АГ, ИБС с полиморфизмом BsmI и/или FokI гена VDR [12,13,14,15,16]. Так, в крупном (n=1211) проспек-тивном исследовании американских мужчин с длительностью наблюдения в среднем 15,3 года, риск АГ составил 1,25 (1,04-1,51) для генотипа BsmI bb по сравнению с генотипом bB или BB гена VDR.…”
Section: Introductionunclassified
“…Результаты исследования корей-ских рабочих выявили противоположные дан-ные, указывающие, что значения систолическо-го и диастолического АД, распространенность АГ выше у лиц с генотипами BB и Bb по срав-нению с генотипом bb [13]. У лиц моложе 65 лет (n=1946) с генотипом BB полиморфного локуса BsmI гена VDR имелся повышенный риск разви-тия инфаркта миокарда (ОШ 1.38 (95% ДИ 1.07-1.79; p=0.016) [14]. Приведенные литературные данные указывают на очевидную роль геноти-пов BsmI и FokI гена VDR в развитии как АГ, так и ИБС, однако имеющиеся различия в полу-ченных результатах в разных странах указыва-ют на необходимость проведения собственных популяционных и региональных исследований.…”
Section: Introductionunclassified